2017
DOI: 10.1007/s11682-017-9722-y
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter and white matter changes in non-demented amyotrophic lateral sclerosis patients with or without cognitive impairment: A combined voxel-based morphometry and tract-based spatial statistics whole-brain analysis

Abstract: The phenotypic heterogeneity in amyotrophic lateral sclerosis (ALS) implies that patients show structural changes within but also beyond the motor cortex and corticospinal tract and furthermore outside the frontal lobes, even if frank dementia is not detected. The aim of the present study was to investigate both gray matter (GM) and white matter (WM) changes in non-demented amyotrophic lateral sclerosis (ALS) patients with or without cognitive impairment (ALS-motor and ALS-plus, respectively). Nineteen ALS-mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 107 publications
2
42
2
Order By: Relevance
“…This structure is proved to participate in motor as well as in cognitive and behavioural functions and plays an important role in neurodegenerative diseases, including ALS (Strick ete al., 2009; for a review see Gellersen et al, 2017). Functional abnormalities and hypometabolism in the cerebellum are well documented in ALS (Ferrer et al, 2016;Buhour et al, 2017) as well as gray and white matter changes, and proven to correlate with cognitive and behavioural symptoms (Tan et al, 2014;Christidi et al, 2017;Thivard et al, 2007). Clinical motor characteristics and possibly cognitive symptoms could be further explained by the involvement of these fALFF and ReHo changes found in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…This structure is proved to participate in motor as well as in cognitive and behavioural functions and plays an important role in neurodegenerative diseases, including ALS (Strick ete al., 2009; for a review see Gellersen et al, 2017). Functional abnormalities and hypometabolism in the cerebellum are well documented in ALS (Ferrer et al, 2016;Buhour et al, 2017) as well as gray and white matter changes, and proven to correlate with cognitive and behavioural symptoms (Tan et al, 2014;Christidi et al, 2017;Thivard et al, 2007). Clinical motor characteristics and possibly cognitive symptoms could be further explained by the involvement of these fALFF and ReHo changes found in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several DTI studies emphasized the significant WM changes in nondemented ALS patients with or without cognitive impairment, explored in the early stages of the disease. [38][39][40] Specifically, the WM abnormalities in the corpus callosum and in the frontotemporal WM tracts, especially in the uncinate and superior longitudinal fasciculi, appeared to be more pronounced in ALS patients with cognitive impairment as compared to those without cognitive impairment, thus revealing more profound alterations in the former group. 39,40 Structural connectivity alterations reflecting neuropathological abnormalities…”
Section: Insights From Diffusion Tensor Mri Studiesmentioning
confidence: 94%
“…29,30,[32][33][34][35][36][37] To note, early extramotor involvement in ALS [18][19][20][21][22][23] and damage of the corticospinal pathway and of the sensorimotor networks in bvFTD 29,30 have been widely recognized. Moreover, since several structural studies have found significant WM extramotor abnormalities in cohorts of ALS patients without profound cognitive decline and explored in relatively early disease stages, 21,[38][39][40] an early damage of extramotor regions in ALS might be a potential marker of clinical symptoms more evident in later disease stages, such as cognitive and behavioral alterations.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study [12] on the CST diffusion profile highlighted the importance of RD in distinguishing between ALS patients and controls on an individual basis. Al-though the great majority of DTI studies on ALS patients showed unchanged AD in CST [5,12,23,[27][28][29][30], a few studies demonstrated an increment [31][32][33] or a decrease [34,35] of this metric within the CST of ALS patients, suggesting that different methodologies, heterogeneity of the cohorts, as well as the intrinsic complexity of UMN alterations can underlie these different results [36].…”
Section: Discussionmentioning
confidence: 99%